Synthesis of Water-Soluble Amphoteric Branched Polymer and Its Temperature and Salt Resistance Performance - Wallner, Gabriel; Granite, Abdallah (Journal of Green Energy and Environmental Engineering, 2026)
The water-soluble amphoteric branched polymers were synthesized by the copolymerization of acrylamide, 2-acrylamido-2-methylpropyl sulfonic acid with N-(3-acrylamidopropyl)trimethylammonium chloride using potassium persulfate and organic amine HMTEA as the initiator through the exothermic reaction system. The influence of synthetic factors was explored to give the optimal synthetic conditions. The structure and aggregation morphology of the copolymers were characterized by infrared spectroscopy, nuclear magnetic resonance spectroscopy, and electron microscopy. The characteristic viscosity of these copolymers was measured using the Ubbelohde viscometer and their molecular weights may be estimated. The viscous behavior of the copolymer solution was studied using a viscometer. The influence of various factors was explored. It was found that the polymer PAAA-1, when added at a polymer concentration of 1500 mg/L, had an apparent viscosity of 19.13 mPa·s at 85°C in a brine solution of 32868 mg/L mineralization. As the salt solution concentration or the temperature increased, the apparent viscosity of the polymer solution decreased. However, the water-soluble amphoteric branched polymers exhibited better salt and heat resistance than the di-component copolymer of acrylamide and 2-acrylamide-2-methylpropyl sulfonic acid.